1988
DOI: 10.1152/ajpheart.1988.255.2.h375
|View full text |Cite
|
Sign up to set email alerts
|

Reabsorption kinetics of albumin from pleural space of dogs

Abstract: The reabsorption of albumin from the pleural space was measured in eight dogs receiving 0.5 ml intrapleural injection of 131I-labeled albumin and a simultaneous intravenous injection of 125I-labeled albumin. Plasma curves for both tracers were obtained over 24 h. The 125I-albumin curve served as input function of albumin for interstitial spaces, including pleura, whereas the 131I-albumin curve represented the output function from pleural space. The frequency function of albumin transit times from pleural space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 0 publications
2
24
0
1
Order By: Relevance
“…2) It was concluded that liquid is preferentially absorbed from areas where stomas are denser, because intrapleurally injected labelled albumin appeared (by gamma camera scannings) to mostly decay from mediastinal, diaphragmatic, and apical regions of dog pleural space [67], but apical regions do not contain stomas [18,19], and part of the measured activity could be due to albumin transferred across the visceral pleura, and eventually removed by lung lymphatics [4,6], not by parietal stomas. Similar considerations, as already observed, apply to the conclusions drawn by MINIATI et al [87].…”
Section: Liquid Exchangessupporting
confidence: 88%
See 2 more Smart Citations
“…2) It was concluded that liquid is preferentially absorbed from areas where stomas are denser, because intrapleurally injected labelled albumin appeared (by gamma camera scannings) to mostly decay from mediastinal, diaphragmatic, and apical regions of dog pleural space [67], but apical regions do not contain stomas [18,19], and part of the measured activity could be due to albumin transferred across the visceral pleura, and eventually removed by lung lymphatics [4,6], not by parietal stomas. Similar considerations, as already observed, apply to the conclusions drawn by MINIATI et al [87].…”
Section: Liquid Exchangessupporting
confidence: 88%
“…The computed value of Jf may vary by orders of magnitude depending on the parameters used. Because at equilibrium liquid inflow and outflow must be equal, conclusions on the relative contributions of the different mechanisms to liquid removal are sometimes drawn, based on the estimated Jf, and vice versa [17,67,87]. These conclusions are obviously affected by large potential errors, and should be taken with caution.…”
Section: Liquid Exchangesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the above findings, the solute-coupled liquid absorption should be due to Na+-K+-ATPase on the interstitial side plus a Na+-H+ and Cl--HCO3-double exchange on the luminal side of the mesothelial cells. Under physiological conditions the solute-coupled liquid absorption (-0-07 ml kg-1 h-'; Agostoni & Zocchi, 1993) seems greater than the lymphatic drainage through the stomata of the parietal pleura (0.02 ml kg-1 h-1; Miserocchi & Negrini, 1986;Miniati, Parker, Pistolesi, Cartledge, Martin, Giuntini & Taylor, 1988), and could be important to keep pleural liquid to a minimum volume. Indeed, on the parietal side it would oppose liquid filtration into the pleural space due to Starling forces, while on the visceral side it would facilitate liquid absorption due to Starling forces (Agostoni & Zocchi, 1990).…”
Section: Introductionmentioning
confidence: 97%
“…Η λεμφαγγειακή ροή από την υπεζωκοτική κοιλότητα σε φυσιολογικές συνθήκες είναι 0.02 mL/Kg/ώρα, όπως υπολογίστηκε σε σκύλους μετά από έγχυση ραδιοσεσημασμένης αλβουμίνης 0.5 mL στην κοιλότητα, ενώ σε κουνέλια είναι μεγαλύτερη 0.07 mL/Kg/ώρα [37,38]. Αυτή αντιπροσωπεύει τη συνολική λεμφαγγειακή ροή από την υπεζωκοτική κοιλότητα που συμπεριλαμβάνει τη ροή μέσω των λεμφαγγείων του διάμεσου ιστού, τα στόματα των λεμφαγγείων του τοιχωματικού υπεζωκότα, καθώς επίσης και την διάχυση και ενδοκυττάρωση [4].…”
Section: ο ρόλος των λεμφαγγείων στην απομάκρυνση του υπεζωκοτικού υγρούunclassified